(untitled) (Sains Humanika, 2008)
The ability for the expansion of domestic as well as international markets requires full commitment from entrepreneurs regardless of the size of the companies. The expansion plans do not only focus on large companies but also, involves Small and Medium Enterprises (SMEs). Although quality and costs are considered as success factors, entrepreneurs have to place a marked emphasis on market assurance issues such as safety and health which are vital in products being marketable as well as the ability in winning market competitions. This literature highlighted the hygiene and food safety practices within food processing SMEs in Malaysia. An aspect of the influence of the food entrepreneurs’ population to the food products quality and safety as well as the food processing standard employed by the SME’s in food processing were discussed in the article. As to accommodate the Malaysia’s Muslim majority population, Halal standard (MS1500:2004) that included food hygiene and food safety, are also discussed in the article, beside the international standards used by the food processing industries.